AN ELECTRONIC BIRTH RECORD MANAGEMENT SYSTEM FOR NIGERIA (Nigerian Journal of Technology, 2019)
Verifying a citizen’s birth information is predominantly weighted with rigorous processes due to the multitude of birth registration centres and the method of birth registration and archiving its records are operationally manual within the nation. Consequently, this approach is systematically prone to destruction, falsification, alteration, or duplication of birth records and thus, this paper proposed and developed an electronic system for birth registration and record management. It adopted the system analysis and design (SAD) methodology suitably for its designs and implementation. The dataflow diagram (DFD) was adopted for its design while its implementation involved several client and server side development tools: Hypertext Markup Language (HTML), Java Script and Cascading Style Sheet (CSS), Hypertext Pre-Processor (PHP) and My Structured Query Language (MySQL). The resultant prototype system was tested and evaluated entirely, and it demonstrated the capability of birth registration, its records management, and also checking its associated challenges – verification, retrieval, duplications, etc. On full deployment, it will curb the rampart falsification of birth information in Nigeria. http://dx.doi.org/10.4314/njt.v38i3.31